Sabilillah dalam Pandangan Syekh Mahmud Syaltut dan Implementasinya dalam Hukum Islam Kotemporer - Ahmad Dzulfikar (Journal of Islamic Civilization, 2020)
This paper reviews the meaning of the phrase sabilillah in the view of Shaykh al-Azhar, Al-Imam Al-Akbar, Shaykh Mahmud Syaltut. Discussing this phrase, Syaltut uses the maudhu'i interpretation method which is implemented in many of his works. By using the library research method, data related to Syaltut thought is collected and analyzed. From these data, the concept of sabilillah in view of Syaltut includes universal values of life established by Islamic law: goodness, justice, cooperation and compassion; and sabilillah is how to realize the objectives of Islamic law itself. With this understanding, Islamic law in the hands of Syaltut appears dynamic in accordance with the context of his era.